A comparative study of the H2-assisted selective catalytic reduction of nitric oxide by propene over noble metal (Pt, Pd, Ir)/γ-Al2O3 catalysts. Issue 2 (June 2016) - Goula, M.A.; Charisiou, N.D.; Papageridis, K.N.; Delimitis, A.; Papista, E.; Pachatouridou, E.; Iliopoulou, E.F.; Marnellos, G.; Konsolakis, M.; Yentekakis, I.V.
Graphical abstract: Highlights: H2 enhances NO conversion of the Pt-, Pd- and Ir-catalyzed C3 H6 -SCR of NO x . H2 -induced de-NO x enhancement follows the sequence: Pt > Ir > Pd. A two-maxima NO conversion pattern is obtained on Pt and Pd, instead of one on Ir. A synergy between H2 and C3 H6 is revealed over Ir, boosting the deNO x performance. Abstract: The impact of H2 as additional reducing agent on the SCR of NO with C3 H6 in excess oxygen, was comparatively explored over low noble metal loading (0.5 wt%), Pt/γ-Al2 O3, Pd/γ-Al2 O3, Ir/γ-Al2 O3 catalysts. To gain insight into the role of H2, the reactions NO + C3 H6  + O2 (R#1), NO + C3 H6  + O2  + H2 (R#2), NO + H2  + O2 (R#3) were employed. In respect to propene oxidation, the Pd > Pt > Ir sequence was obtained under R#1, since they exhibit complete conversion at 220, 250, 325 °C, respectively; all metals exhibit moderate deNO x performances ( X NO, <40%). H2 co-presence (R#2) promotes both the NO and C3 H6 conversions, which is valid in the whole temperature interval investigated (50–400 °C), being more substantial for Pt/γ-Al2 O3 and Ir/γ-Al2 O3, less beneficial for Pd/γ-Al2 O3 . A two-maxima feature is obtained on X NO pattern (at ∼100 and ∼230 °C) of Pt and Pd during R#2. The low temperature maximum −attributed to NO reduction by H2 - is substantially more pronounced on Pt than Pd, offering X NO ∼90% and SN2 ∼85%; the high temperature maximum—attributed to NO reduction by C3 H6 —is higher by ∼15% on both Pt and Pd, in respect to the values obtained during R#1, while SN2 remained unaffected. Different X NO pattern with one maximum is obtained over Ir, implying a synergistic interaction between H2 and C3 H6 . This synergy is accompanied by a substantial widening of the NO reduction window toward lower temperatures and a considerable increase on both X NO, max and SN2 (from X NO ∼30% with SN2 ∼55% during R#1 to X NO ∼70% with SN2 ∼95% during R#2). The specific features of all reactions and metals employed are comparatively discussed.